Gender Differences in Antibiotic Prescriptions and Healthcare Visits Among Caregivers Accompanying Children with Respiratory Tract Infections: A Cross-Sectional Study - Taito Kitano; Yusuke Asai; Ryuji Koizumi; Norio Ohmagari; Shinya Tsuzuki (Infectious Diseases and Therapy)
Abstract Introduction Women are more often prescribed antibiotics than men for a number of health conditions. Adults’ behaviours in engaging with healthcare for themselves, especially when attending appointments with a child with a respiratory tract infection for whom they provide care, may contribute to the gender differences in antimicrobial use. This study aimed to evaluate gender differences in caregivers’ attendance at healthcare visits for children with respiratory tract infections, their behaviours in engaging with healthcare for themselves and their children, and associated antibiotic prescriptions. Methods An online survey was conducted among Japanese caregivers, asking about children’s healthcare visits and prescriptions for antimicrobials associated with respiratory tract infections, who accompanied them and whether the caregiver attended a simultaneous healthcare visit for themselves. We used multivariable logistic regression analysis to evaluate factors associated with caregivers’ attendance at children’s healthcare visits and responders’ simultaneous healthcare visits. Results Among the 1664 participants, 1091 accompanied their children to healthcare visits. Female responders were significantly more likely to accompany their child (adjusted odds ratio (aOR) 6.76 [95% confidence interval (CI) 5.00–9.15], p < 0.001). Participants with higher education levels were less likely to require a simultaneous healthcare visit (aOR 0.56 [95% confidence interval (CI) 0.33–0.94], p = 0.029). Other covariates, including participants’ gender, were not significantly associated with simultaneous healthcare visits. Conclusion Women were more likely to accompany a child to a healthcare visit for a respiratory tract infection. However, they were no more likely to require a simultaneous healthcare visit, or receive antibiotics at those simultaneous visits.